Paradigms shift in business perspectives: Offline to Online - Sharma, Isha; Mukherjee, Tarun Tapas; Satpathy, Dr Swayam Prabha (The journal of contemporary issues in business and government, 2023)
In the twenty-first century, people lack the opportunity to meet up and draw in with each other. Social media Platforms help individuals in associating person-to-person communication, and permitting them to remain associated in any event, when they are physically isolated. Aside from that, social media platforms encourage strong bonds major between the product and the individual, bringing about critical promoting potential via blogs or day to day updates. It likewise gives an opportunity to post remarks on any occasion that must be communicated and can be utilized as a special promotional instrument for client adoption as well as marketing. Small start-ups owners are now gaining followers and subscribers by directing customers to their social media profile as there is an upper hand over other famous public media, for example, TV, these media enjoy a serious benefit. Through this medium, new ways of doing business have emerged where those who have the opportunity to start a business do not have to take on too much infrastructure, investment, or risk. This study aims to investigate the phenomenon of this new entrepreneur. It is unquestionable that people do not find time to interact with each other. One of the most significant developments of internet and social media, people can remain connected to each other and create loyal connections to their companions.